(untitled) (Journal of the College of Basic Education, 2022)
Locating transmitters optimally in a radio network, to guarantee a stipulated quality of service (QOS), is a network performance (NP) hard combinational problem. Regarding a known area, choosing transmitter locations among alternatives is tackled by a coarse-grained parallel genetic algorithm, which maximize the coverage together with reducing the number of utilized transmitters. In this paper, an effective local search operator is raised, and the affection of the neighbor topology is compared. Simulations on a dedicated cluster demonstrate that contrasting to existent algorithms, the parallel GA improves the optimizing quality and speed greatly.